Analisis Partisipasi Siswa Dalam Menjaga Kesehatan Lingkungan Ditinjau Melalui Kecerdasan Naturalis - Istiana, Rita; Pratama, Wisnu Surya; Hidayat, Nandang (Jurnal Pendidikan Biologi, 2017)
This study was a mixed method sequential explanatory research. This study aimed to obtain information of a relationship between naturalist intelligence and studentsâ participation in maintaining environmental health and the other factors which influence it. This study was conducted from February to October 2017. The analysis unit was 169 students of one of public junior high school in South Bogor District. Quantitative research results showed that correlation coefficient (ry) between naturalist intelligence and studentsâ participation in maintaining environmental health was 0,407. This value showed that naturalist intelligence have quite a high contribution to studentsâ participation in maintaining environmental health. Qualitative research results showed that there are the other factors which can influence studentsâ participation in maintaining environmental health, such as social interaction with their friends in the home or school environment, studentsâ understanding of important functions of living things, studentsâ habit and self-awareness, and guidance from both parents and teachers.Â Keywords: participation, environmental health, intelligence, naturalist intelligence